Pemahaman Pedagogik Guru dalam Mengajar Anak Berkebutuhan Khusus di Sekolah Inklusi - Leonita Dwi Agustin; Weny Savitry S. Pandia (Provitae: Jurnal Psikologi Pendidikan, 2014)
Teachers in inclusive schools are required to have a pedagogic knowledge inspecial needs children. Teachers must have knowledge about characteristics ofspecial needs children, construct and apply learning intervention for specialneeds children, and construct and apply evaluation for special needs children.This research was designed to know teachers’ pedagogic knowledge forspecial needs children in inclusive schools. Participants are teachers fromPublic Elementary School X which is an inclusive school. Research indicatedthat teachers have lack knowledge about characteristics of special needschildren. Teachers didn’t know how to construct and apply learningintervention and evaluation for special needs children. Evaluations are giventhrough tests and adaptation of Kriteria Ketuntasan Minimal (KKM). Theseare the results of lack teachers’ pedagogical knowledge. Therefore, researcher designed a training to give pedagogical knowledge for teaching special needs children in inclusive children to the participants. Training materials including characteristics, assessment, and identification of special needs children, and construct Individual Education Program (IEP).Keywords: teachers pedagogical competence, inclusive schools, special needs children